PARTISIPASI ORANG TUA TERHADAP PELAKSANAAN PROGRAM SEKOLAH RAMAH ANAK (SRA) DI SD RAMAH ANAK KABUPATEN SLEMAN - Wulandari, Tati; Nirwana, Iin; Nurlinda, Nurlinda (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2022)
This study aims to determine the participation of parents in the implementation of child-friendly school programs. This research is a qualitative research using a case study approach. Interview guidelines and questionnaire sheets were used as instruments to obtain data regarding parental participation. Parental participation was investigated based on the implementation standards of child-friendly school programs. There are five formulations of research results based on the forms of participation carried out by parents in the implementation of child-friendly school programs (1) Sending children to school close to parents (home/office), (2) Providing quality time at least 20 minutes a day on a regular basis to listen to and respond to children, (3) Provide time, thought, energy, and materials according to ability to ensure the growth and development, interests, talents, and abilities of children, (4) Supervise children's safety, safety, and comfort including ensuring healthy internet and social media use child-friendly, (5) Communicating intensively with the school.